Analisis Peran Digital Marketing terhadap Peningkatan Kunjungan Wisatawan di Pantai Bagedur Malingping - Fauz Faudziah; Munawaroh Munawaroh (Jurnal Manajemen dan Ekonomi Kreatif, 2025)
Bagedur beach in Malingping is one of the tourist destinations that has great potential to attract tourists. However, the lack of information makes tourist visits still a challenge. Digital marketing is now a strategic solution in promoting tourist destinations, including Bagedur Beach. This study aims to analyze the role of digital marketing applications in increasing tourist visits at Bagedur Beach. Through a qualitative method with a case study approach, data is collected through observation, interviews, and literature studies. The results of the study show that the use of digital marketing applications, such as social media and online booking platforms, contributes significantly to the increase in tourist visits. This application not only helps in wider promotions but also in making it easier to access information for prospective tourists. The recommendation of this study is that tourism managers need to be more active in utilizing digital marketing applications to increase the attractiveness of tourist destinations.